Curcumin-based Antioxidant and Glycohydrolase Inhibitor Compounds: Synthesis and In Vitro Appraisal of the Dual Activity Against Diabetes - Esmaeili, Sajjad; Ghobadi, Nazanin; Nazari, Donya; Pourhossein, Alireza; Rasouli, Hassan; Adibi, Hadi; Khodarahmi, Reza (Medicinal Chemistry, 2021)
Background: Curcumin, as the substantial constituent of the turmeric plant (Curcuma longa), plays a significant role in the prevention of various diseases, including diabetes. It possesses ideal structure features as an enzyme inhibitor, including a flexible backbone, hydrophobic nature, and several available hydrogen bond (H-bond) donors and acceptors. Objective: The present study aimed at synthesizing several novel curcumin derivatives and further evaluation of these compounds for possible antioxidant and anti-diabetic properties along with inhibitory effect against two carbohydrate-hydrolyzing enzymes, α-amylase and α-glucosidase, as these enzymes are therapeutic targets for attenuation of postprandial hyperglycemia. Methods: Therefore, curcumin-based pyrido[2,3-d]pyrimidine derivatives were synthesized and identified using an instrumental technique like NMR spectroscopy and then screened for antioxidant and enzyme inhibitory potential. Total antioxidant activity, reducing power assay and 1,1-diphenyl-2- picrylhydrazyl (DPPH•) radical scavenging activity were done to appraise the antioxidant potential of these compounds in vitro. Results: Compounds L6-L9 showed higher antioxidant activity while L4, L9, L12 and especially L8 exhibited the best selectivity index (lowest α-amylase/α-glucosidase inhibition ratio). Conclusion: These antioxidant inhibitors may be potential anti-diabetic drugs, not only to reduce glycemic index but also to limit the activity of the major reactive oxygen species (ROS) producing pathways.
Keywords: diabetes